A minimized falling damage method for humanoid robots. (5th September 2017) - Li, Qingqing; Chen, Xuechao; Zhou, Yuhang; Yu, Zhangguo; Zhang, Weimin; Huang, Qiang
In order to better adapt to human living environment for improving the ability of serving people on various occasions, humanoid robots need to prevent themselves from being severely damaged during falling backward. In this article, we have study the law of human falling motion with a motion capture system and propose a minimized falling damage method for humanoid robots. Falling backward is divided into two phases: the falling phase and the touchdown phase. The parametric optimal strategy based on inverted pendulum with flywheel is used to plan the motion of robot in the first phase to reduce the impact. In the second phase, to prevent the robot from bouncing and rolling over, the heuristic strategy including the best ratio of leg length inspired by biomechanical is adopted. The experiments have been tested on the BIT Humanoid Robot 6 prototype platform and the presented method has been validated.